CRYPTOCURRENCY PERSPECTIVE: THE DRIVERS LEADING FROM AWARENESS TO ADOPTION- A CASE OF PAKISTAN - Ashraf, Ayesha; Manzoor, Alia; Liaquat, Malka; Yasmeen, Najma (The journal of contemporary issues in business and government, 2021)
Purpose: The purpose is to add constructive points in the existing literature by identifying drivers that encompass the journey from creating awareness tothe ultimate adoption of the cryptocurrency payment system. Methodology: Certain aspects from the TAM Model, Innovation of Diffusion Theory, & AIDA Model are synthesized to form a holistic framework. To test the model, data from 250 digital banking users was collected via survey method and analysed through SEM. Originality: This study has significance for marketers, traders, digital banking users, and ultimate buyers of cryptocurrency as it would help them identify which areas need to be addressed for tackling early adopters Findings: Personal level characteristics significantly influence awareness, and adoption of cryptocurrencies. Perceived benefits and risks associated with the use of cryptocurrencies moderates the relationship between crypto-currency awareness and its adoption. Implications:The multi-perspective framework is believed to synthesize debates and discussions in the existing literature and provide the basis for future research.